BENTUK PENYAJIAN TARI TAK OYAI PADA PESTA MALAM BAINAI DI KANAGARIAN PAINAN TIMUR KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Syaputra, Hengky Novri; Darmawati, Darmawati; Desfiarni, Desfiarni (SENDRATASIK UNP, 2019)
AbstractThis article aimed to reveal and describe the Forms of Tak Oyai Dance Presentation at the Malam Bainai Party in East Painan Village, IV Jurai District, Pesisir Selatan Regency.. The type of this research was qualitative research using descriptive analysis methods. The types of data in this research were primary and secondary data. The main instrument in this study was the researcher himself and assisted with supporting instruments such as stationeries and camera. Technique of data collection were carried out by literature studies, observations, interviews and documentations. In analyzing the data, there were two steps, namely describing the dance elements contained in the Tak Oyai dance, then describing the sequences of the Tak Oyai dance event that were found in the Malam Bainai party. The results showed that the Tak Oyai dance was one of the traditional dances located in East Painan Village, IV Jurai District, Pesisir Selatan Regency. Tak Oyai dance consisted of 6 different types of movements and might be danced by even numbers of male and female dancers. Tak Oyai dance used internal music, namely dendang music sung by an artist named Amlis who was the heir of Tak Oyai, and the dance used adok which was used as a symbol to express his sense of joy in doing activities. The form of the presentation of Tak Oyai dance at Malam Bainai party was begun with the reading of the Holy Qur'an, then picking up the bride followed by an apology to the parents, then continued by the Tak Oyai dance performance. Then, the last action was putting on inai.Keywords: presentation, Tak Oyai dance, Malam Bainai Party